Um estudo descritivo-analítico do Manual de Análise Léxica e Sintática de José Oiticica - Sapaterra, Ana Paula (2015)
This thesis has the aim to describe and analyze the José Oiticica s Lexical and Syntactic Manual Analysis work. For this work we examined all the twelve editions and we certified that the first four ones remained similar in the linguistic aspects. From the fifth one, there was partial a redoing of the work, fact that was kept to the twelfth edition (1958), this was the reason we chose to compare the first (1919) and the fifth (1940) in order to point the permanence and the changes ocurred among the versions. We observed that the second, third and fourfh editions had some improvements , adding morphosis, flexons, root and radical on the second edition definitions, the junction of the two paragraphs in one just and the adding of an erratum on the second edition. These modifications that ocurred from the second to the fourth one don t mean that the volumes were modifyed on the contents; From the fifth edition the redoing of the work was done, like the figure alteration , reason which we were taken to compare the version of 1919 and 1940. We also point the motive of the Manual prodution and for those who it was destined. To develop this research, it was necessary to survey the historical situation of Brazil in the First Republic and the facts that became fundamental on the nation development so idealized by the republicans and, subsequent to challenged, by the anarchists. Some aspects of José Oiticica s life will be approached from the cultural and social spaces were he passed by, about the job that he did as an educator, journalist and writer, about the works produced by him, the turmoils that he suffered due to his engagement with the anarchist ideal. For this we will use as theoretic apparatus the linguistic Ideas History (Auroux, Fávero and Orlandi), in order to seize in the chosen subject - the José Oiticica s Manual - , how and what shape he and the environment are linked in a cause and effect relationship